Complexities of project interactions in Nicaraguan rural development - Robinson, Sara (2010)
Empowerment has become an eloquent catchphrase in many development projects. While commonly used, the implications of empowerment in development work have been criticized because of the inherent assumption that someone has the power to give power to another. At the same time, small scale farmers have been identified as key figures not only in rural development, but also for national economic stability and growth. However, in reality rural communities are largely left out of the design and implementation of the very projects that intend to contribute to rural people’s empowerment. By relying on theoretical roots of the meanings of empowerment from community psychology, education and other fields, this study focuses on the need of all to feel empowered, all gaining possibilities to empower oneself and contribute to empowering opportunities for others. The aim is to explore contextual meanings of empowerment and the collaborative relationships built between rural communities and development agencies through projects as the medium, while recognizing varying levels of complications within project interactions. Intrapersonal empowerment in this research has been the first to be impacted at greater levels, even in the case where structural, governmental, managerial, spatial and time complications have kept the program from achieving many of its intended goals. Still, empowerment can flourish with personal involvement, both men and women’s participation as well as caring and respectful interactions in project work. Through my qualitative fieldwork in Nicaragua, I consider questions over the notions of ‘empowerment’ and focus on factors of empowering conditions within project complexities. This case study approach, carried out primarily through methods of participant observation and interviews, scrutinized the following aspects of empowerment: learning through interaction and project processes from both community and organizational perspectives, ownership and vision as well as participant involvement.